Comparison of Factors Affecting on KDML 105 Rice Production According to GAP Standard of Individual and Group Farmers in Mahasarakham Province - Kwang-Ngoen, P.; Limnirankul, B.; Sirisunyaluck, R. (International Journal of Agricultural Technology, 2018)
The purpose of this research was to study the comparison of factors affecting on KDML 105 rice production according to GAP standard of individual and group farmers in Mahasarakham province. The populations in this research were 120 individual farmers and 55 group farmers. Data were collected through structured questionnaire interview. Data analyzed by using frequency, percentage, mean, standard deviation and t-test. The results showed that the comparison of some factors between individual and group farmers were significant differences in the promotion and supporting services in KDML 105 rice production according to the GAP standards, the opinions on the implementation of the GAP guidelines for production and the satisfaction on the enhancement of knowledge skills in rice production technology according to GAP standard. Group farmers were promoted and supported in rice production according to GAP standards better than individual farmers. Also they had better opinions than individual farmers. But in contrast to individual farmer was more satisfied with the improvement of their knowledge skills on rice production technology according to GAP standards than group farmer.